Interaction of spin-orbit angular momentum in the tight focusing of structured light - Guo, Ji-Xiang; Wang, Wen-Yue; Cheng, Tian-Yu; Lü, Jia-Qi (Frontiers in Physics, 2022)
As an intrinsic property of light, angular momentum has always been an important research object of light field. In the past few years, the interactions between spin angular momentum and orbital angular momentum in tightly focused structured light have attracted much attention. Different from the independent conservation in the paraxial condition, the polarization-dependent spin angular momentum and the phase-dependent orbital angular momentum are coupled under tight focusing condition based on different physical mechanisms. The research on spin-orbit interaction will be helpful to deeply understand the nature of photon as well as extend the applications of light. Here, different forms of spin-orbit interaction during the tight focusing of structured light have been briefly introduced and classified. Besides, the existing problems and development prospects in the research about spin-orbit interaction of light are discussed, including the quantitative detection of the local distribution of optical spin and orbital angular momentum in experiments and the further applications of spin-orbit interaction.